2018
DOI: 10.21608/ejss.2018.6151.1216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Manure Combinations on Performance and Rot Infection of Stressed-Jerusalem Artichoke Plants

Abstract: T HIS investigation was carried out for two summer seasonsof 2016/2017 and 2017/2018 to investigate the influence of three types of organic manures;farmyard (FYM),poultry (PLM) and pigeon manures(PGM) and their combinationson southern blight disease incidence (caused by Sclerotiumrolfsii), some vegetative growth characters, chemical constituents, yield and its components of Jerusalem artichoke (Helianthus tuberosus L.)plants grown under saline and calcareous soils. The results indicated that T 8 (75% PGM + 25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Excessive nitrogen fertilization and low soil pH contribute to the development of S. sclerotiorum, whereas S. rolfsii thrives in moist and warm environments [16]. Avad and Ahmed [64] analyzed the influence of three types of fermented organic fertilizers, including farmyard, poultry and pigeon manure, and their combinations on the incidence of southern blight (caused by Sclerotium rolfsii), vegetative growth parameters, chemical composition, yield, and yield components in Helianthus tuberosus L., and found that all fertilizer combinations minimized the severity of infections.…”
Section: Mycological Analyses Of Tubers and Aerial Plant Partsmentioning
confidence: 99%
“…Excessive nitrogen fertilization and low soil pH contribute to the development of S. sclerotiorum, whereas S. rolfsii thrives in moist and warm environments [16]. Avad and Ahmed [64] analyzed the influence of three types of fermented organic fertilizers, including farmyard, poultry and pigeon manure, and their combinations on the incidence of southern blight (caused by Sclerotium rolfsii), vegetative growth parameters, chemical composition, yield, and yield components in Helianthus tuberosus L., and found that all fertilizer combinations minimized the severity of infections.…”
Section: Mycological Analyses Of Tubers and Aerial Plant Partsmentioning
confidence: 99%